Survey evidence on conditional norm enforcement - Christian Traxler; Joachim Winter (Max Planck Institute for Research on Collective Goods, 2009)
We discuss survey evidence on individuals' willingness to sanction norm violations such as evading taxes, drunk driving, fare dodging, or skiving off work by expressing disapproval or social exclusion. Our data suggest that people condition their sanctioning behavior on their belief about the frequency of norm violations. The more commonly a norm violation is believed to occur, the lower the individuals' inclination to punish it. Based on an instrumental variable approach, we demonstrate that this pattern reflects a causal relationship.
Keywords: K42; Z13; D1; 360; Norm Enforcement; Sanctioning; Social Norms; Survey Evidence; Rechtsdurchsetzung; Strafe; Soziale Norm; Befragung; Theorie; Deutschland